A pilot study on temporal changes in IL-1β and TNF-α serum levels after spinal cord injury: the serum level of TNF-α in acute SCI patients as a possible marker for neurological remission - Biglari, Bahram; Swing, T.; Child, Christopher; Büchler, Axel; Westhauser, Fabian; Bruckner, Thomas; Ferbert, Thomas; Gerner, Hans-Jürgen; Moghaddam-Alvandi, Arash (Spinal cord, 2015)
Serum levels of interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α) were measured over a 12-week period in 23 patients with spinal cord injury (SCI) with and without neurological improvement.
Gesehen am 25.05.2020